Pengaruh Pemberian Kompesansi Langsung Dan Tidak Langsung Terhadap Kinerja Karyawan Cv. Semi Baru Samarinda - Heriyanto . (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
"The Effect of Direct and Indirect Compensation on Employee Performance CV. New Semi Samarinda "The purpose of this analysis is to determine how much influence kompensansi directly and indirectly to the performance of an employee CV . New semi Samarinda . As a trading company that is large enough , then the CV. New semi Samarinda provide better compensation system for its employees , so that the employee's performance can also be improved by working well with good results, in the form of a high level of sales in the sales results. To determine the influence of the compensation (direct and indirect) to increase employee productivity , then this analysis using multiple linear regression analysis tools.